Upregulation of BCAM and its sense lncRNA BAN are associated with gastric cancer metastasis and poor prognosis. Issue 4 (13th February 2020) - Jin, Juan; Xie, Shanshan; Sun, Qiang; Huang, Zhenxia; Chen, Kanghua; Guo, Dongyang; Rao, Xianping; Deng, Yujie; Liu, Yiman; Li, Shuang; Cui, Wenyu; Maibam, Valentina Chanu; et al.
Abstract : Patients with metastatic gastric cancer (GC) have a poor prognosis; however, the molecular mechanism of GC metastasis remains unclear. Here, we employed bioinformatics to systematically screen the metastasis‐associated genes and found that the levels of basal cell adhesion molecule ( BCAM ) were significantly increased in GC tissues from patients with metastasis, as compared to those without metastasis. The upregulation of BCAM was also significantly associated with a shorter survival time. Depletion of BCAM inhibited GC cell migration and invasion. Knockout (KO) of BCAM by the CRISPR/Cas9 system reduced the invasion and metastasis of GC cells. To explore the mechanism of BCAM upregulation, we identified a previously uncharacterized BCAM sense lncRNA that spanned from exon 6 to intron 6 of BCAM, and named it as BCAM ‐associated long noncoding RNA ( BAN ). Knockdown of BAN inhibited BCAM expression at both mRNA and protein levels. Knockdown of BAN suppressed GC cell migration and invasion, which was effectively rescued by ectopic expression of BCAM . Further clinical data showed that BAN upregulation was associated with GC metastasis and poor prognosis. Importantly, BAN expression was also significantly associated with that of BCAM in GC tissues. Taken together, these results indicate that increased expression of BCAM and its sense lncRNA BAN promote GC cell invasion and metastasis, and are associated with poor prognosis of GC patients. Abstract : We found that the levels of BCAM and its sense lncRNA BAN were increased in gastric cancer (GC) tissues with metastasis. Knockdown of BAN inhibited BCAM expression at both mRNA and protein levels. Moreover, increased expression of BCAM and its sense lncRNA BAN promote GC cell invasion and metastasis, and are associated with poor prognosis of GC patients.